Phylogenetic diversity of geometrid moths decreases with elevation in the tropical Andes. Issue 11 (26th April 2013) - Brehm, Gunnar; Strutzenberger, Patrick; Fiedler, Konrad
Abstract : Species diversity of geometrid moths (Lepidoptera, Geometridae) has previously been shown to be extremely and constantly high along a continuously forested elevational gradient in the Andes of southern Ecuador. We analysed samples taken from 32 sites between 1999 and 2011 in northern Podocarpus National Park and adjacent areas from 1020 to 2916 m a.s.l. We conjecture that high elevation habitats were historically mostly colonised by species from lower elevations, and that environmental filtering (e.g. through host plant specificity or temperature tolerance) constrained colonisation from lower elevations, which would yield a pattern of elevationally decreasing phylogenetic diversity. We analysed elevational phylogenetic patterns by means of: 1) the nearest‐taxon index (NTI), 2) DNA barcode‐based terminal branch lengths (TBLs) from maximum‐likelihood phylogeny, 3) the subfamily composition of the local assemblages, and 4), the rarefied number of morphologically defined genera per site. We counted a total of 1445 species. NTI values significantly increased with elevation, both in a conventional and a rarefaction approach. TBLs decreased significantly with elevation. Subfamily composition profoundly changed with elevation, particularly expressed as an increased proportion of the subfamily Larentiinae and decreased fractions of Sterrhinae and Geometrinae. The number of genera in equally rarefied species resamples significantly decreased with elevation. We conclude that environmental filtering indeed contributed to an altitudinal decrease in moth phylodiversity, but these constraints prevented only relatively few clades from colonising high elevation habitats.